„Mały Dziennik” jako przedsięwzięcie medialne. Geneza i zarys charakterystyki czasopisma - Pietkiewicz, Jakub (Acta Universitatis Lodziensis. Folia Historica, 2015)
The article presents the reader in the characteristics of the press market in the Second Republic of Poland, the characteristics of Catholic publishers and the impact of the most important Catholic publishing center in Niepokalanów – Franciscans. However, it applies to, above all, one of the most popular newspapers of the interwar period, and also the most popular Catholic daily newspaper. The text describes the genesis of „Mały Dziennik” magazine and the effort of creator (Franciscans) associated with its publication. Moreover, the article presents the development of the publishing house, editorial board, as well as the newspaper and its evolution over the years 1934–1939. Furthermore, it shows the reactions of different political and social environments and newspapers on the creation of this newspaper and its content. It also presents the behind-the-scenes work of editorial board, including changes in its composition, publishing schedule, methods of distribution, acquisition of readers and subscribers, as well as advertisers. The article describes the main groups of topics covered in the newspaper and main regular columns (related to events in the world, in Poland, in the Church, etc.). It separately shows the method of advertising products in this newspaper and conducting promotional campaigns. It describes the most important social events conducted by the newspaper. The author also characterizes the ideological background of the newspaper connected with the orthodox and nationally oriented Catholicism.